Can influenza H1N1 vaccination lead to the membranous glomerulonephritis? - Ali Kutlucan; Ibak Gonen; Esra Yildizhan; Yusuf Aydin; Tansu Sav; Umran Yildirim (Wolters Kluwer Medknow Publications, 2012)
In 2009 winter, Influenza A (H1N1) monovalent split virus vaccine was used prevalently in the whole world as a result of the pandemic caused by Influenza (H1N1) virus. The vaccine's adverse effects were observed closely and vaccination has been found as safe in most studies. But some reports about immune response related diseases after influenza vaccinations are remarkable. The close relationship between membranous glomerulonephritis and antigens is known, particularly in seconder forms which occur after viral infections and vaccinations. So this case report is about a 56-year-old man, who developed membranous glomerulonephritis 23 days after the vaccination against Influenza A (H1N1) virus.